Jeszcze o możliwościach przewidywania zmian językowych = Yet on the possibilities of predicting linguistic changes - Walczak, Bogdan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is a continuation of the paper devoted to forecasting the future of the language, delivered on October 14, 2015 at the Word Culture Forum in Bydgoszcz. It mainly concerned Zdzisław Stieber`s English-language work entitled "On the predictability of linguistic changes".
Keywords: historia języka; przyszłość polszczyzny; zmiany językowe; liczba podwójna; kompetencja językowa; history of language; the future of the Polish language; linguistic changes; double number; linguistic competence